On the relationship among linear type traits and functional longevity in the Italian Mediterranean buffalo using a Weibull proportional hazards model - M. Gómez-Carpio; D. Rossi; R. Cimmino; Y. Gombia; D. Altieri; R. Di Palo; G. Campanile; S. Biffani; G. Neglia (Journal of Dairy Science)
ABSTRACT: The Weibull proportional hazards model was used to identify the nongenetic effects that affect length of productive life (LPL) of the Italian Mediterranean buffalo. Data were provided by the Italian National Association of Buffalo Breeders and included records of reproductive, productive, and linear type traits from 59,943 buffalo with first calving from 2002 to 2019. Data were divided into 4 geographical regions to determine whether the relationship between the investigated effects and LPL varied by region. Length of productive life was defined as the number of days from the first calving to culling for those buffaloes that were culled (uncensored) or to the date of the last test-day for those that are still alive (censored). The Weibull model included time-dependent effects of herd-year-season of calving, parity and stage of lactation, production as within-herd deviations, as well as time-independent effects of age at first calving, year of birth, type of reproduction (natural mating vs. AI), classifier, and ten linear type traits. The average duration of productive life was 1,604 days. Both year of birth and production level had a significant effect on culling risk. Moreover, culling risk decreased linearly across parities. The reference point for age at first calving relative to other classes was set at 35 months. A significant relationship between linear type traits and relative culling risk was also observed, being highest for buffaloes with the lowest linear scores. The results show that the Weibull model provides consistent and robust risk estimates. Therefore, this model would be recommended for future implementation of the first genetic evaluation of LPL in the Italian Mediterranean buffalo.